2021
DOI: 10.1101/2021.11.05.465336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Immune Signatures Data Resource: A compendium of systems vaccinology datasets

Abstract: Vaccines are among the most cost-effective public health interventions for preventing infection-induced morbidity and mortality, yet much remains to be learned regarding the mechanisms by which vaccines protect. Systems immunology combines traditional immunology with modern ‘omic profiling techniques and computational modeling to promote rapid and transformative advances in vaccinology and vaccine discovery. The NIH/NIAID Human Immunology Project Consortium (HIPC) has leveraged systems immunology approaches to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…These datasets were compiled into ImmPort , an NIH-funded repository for immunological data 27 , and uploaded to ImmuneSpace (http://www.ImmuneSpace.org) for centralized QC and processing (Figure 1A). This combined database, named the Immune Signatures Data Resource 26 , includes responses to a broad range of vaccines, including live-attenuated viruses (e.g. yellow fever, smallpox and influenza vaccines), recombinant viral vectors (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These datasets were compiled into ImmPort , an NIH-funded repository for immunological data 27 , and uploaded to ImmuneSpace (http://www.ImmuneSpace.org) for centralized QC and processing (Figure 1A). This combined database, named the Immune Signatures Data Resource 26 , includes responses to a broad range of vaccines, including live-attenuated viruses (e.g. yellow fever, smallpox and influenza vaccines), recombinant viral vectors (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we have demonstrated that meta-analysis of vaccine trials can provide valuable insights into the common and unique aspects of immune responses across vaccines. Combined with the Immune Signatures Data Resource 26 , these computational approaches and repositories will enable future research into the mechanisms of vaccine-induced immunity to inform development of improved adjuvants and vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations